Transcriptional Regulation of ING5 and its Suppressive Effects on Gastric Cancer - Zheng, Hua-chuan; Xue, Hang; Wu, Xin; Xu, Hai-lan; Zhao, En-hong; Cui, Zheng-guo (Frontiers in Oncology, 2022)
ING5 targets histone acetyltransferase or histone deacetylase complexes for local chromatin remodeling. Its transcriptional regulation and suppressive effects on gastric cancer remain elusive. Luciferase assay, EMSA, and ChIP were used to identify the cis-acting elements and trans-acting factors of the ING5 gene. We analyzed the effects of SAHA on the aggressive phenotypes of ING5 transfectants, and the effects of different ING5 mutants on aggressive phenotypes in SGC-7901 cells. Finally, we observed the effects of ING5 abrogation on gastric carcinogenesis. EMSA and ChIP showed that both SRF (−717 to −678 bp) and YY1 (−48 to 25bp) interacted with the promoter of ING5 and up-regulated ING5 expression in gastric cancer via SRF-YY1-ING5-p53 complex formation. ING5, SRF, and YY1 were overexpressed in gastric cancer, (P<0.05), and associated with worse prognosis of gastric cancer patients (P<0.05). ING5 had positive relationships with SRF and YY1 expression in gastric cancer (P<0.05). SAHA treatment caused early arrest at S phase in ING5 transfectants of SGC-7901 (P<0.05), and either 0.5 or 1.0 μM SAHA enhanced their migration and invasion (P<0.05). The wild-type and mutant ING5 transfectants showed lower viability and invasion than the control (P<0.05) with low CDC25, VEGF, and MMP-9 expression. Gastric spontaneous adenocarcinoma was observed in Atp4b-cre; ING5f/f, Pdx1-cre; ING5f/f, and K19-cre; ING5f/f mice. ING5 deletion increased the sensitivity of MNU-induced gastric carcinogenesis. ING5 mRNA might be a good marker of gastric carcinogenesis, and poor prognosis. ING5 expression was positively regulated by the interaction of SRF-YY1-ING5-p53 complex within the ING5 promoter from −50 bp upstream to the transcription start site. ING5 deletion might contribute to the tumorigenesis and histogenesis of gastric cancer.